1991
DOI: 10.1042/bj2730449
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies as probes for ligand gating of single sarcoplasmic reticulum Ca2+-release channels

Abstract: A large (565 kDa) junctional sarcoplasmic reticulum (SR) protein, the ryanodine receptor (RYR), may play both a structural and a functional role in the mechanism of skeletal muscle excitation-contraction coupling. Recently, the primary amino acid sequence of the RYR has been elucidated. In this paper, we introduce an immunological approach to examine the functional (electrophysiological) properties of the RYR when it is incorporated into planar lipid bilayers. The effects of two polyclonal antibodies against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Thus, the binding of the antibody may not affect the ryanodine binding activity of RyR. We could not exclude the possibility that the antibody might alter the properties of RyR channels as previously reported (38,39), because we could not obtain Ryr3 without complex formation with the antibody. However, well-consistent properties of ryanodine binding with those of bullfrog ␤-RyR (Fig.…”
Section: Fig 7 Estimation Of the Fractional Amount Of Ryr3 In Rabbimentioning
confidence: 79%
“…Thus, the binding of the antibody may not affect the ryanodine binding activity of RyR. We could not exclude the possibility that the antibody might alter the properties of RyR channels as previously reported (38,39), because we could not obtain Ryr3 without complex formation with the antibody. However, well-consistent properties of ryanodine binding with those of bullfrog ␤-RyR (Fig.…”
Section: Fig 7 Estimation Of the Fractional Amount Of Ryr3 In Rabbimentioning
confidence: 79%
“…25 In addition, Fill et al have indicated that polyclonal antibodies directed against the region 4445-4586, in RyRl, could reduce the open probability of the channe1. 26 More recently, an affinity purified antibody directed against epitopes present between residues 4478-4512 (sequence 13C2), was shown to increase the calcium sensitivity of RyRl incorporated into planar lipid bilayers, without moddying the Mg2+, ATP, Ry, and ruthenium red modulation.l9 When the 13C2 antibody was further affinity purified on the peptide sequence PEPEPEPEPE (13C2pl) included in the 13C2 fragment, it was shown, in single channel recording experiments, to specifically inhibit calcium binding and to inhibit calcium or caffeine channel activation, without affecting ATP dependent channel activity.20 It appears that the PE repeated motif is a high affinity calcium binding domain, which can be blocked by a specific antibody. When other epitopes near the PE repeat are targeted by the anti-13C2 antisera a possible local conformational change could be responsible for an increased calcium binding affinity and calcium-sensitivity.20 A different polyclonal antibody, reacting against residues 4380-4625, which contain the PE repeat, was also shown to decrease dexorubicin and calciuminduced calcium release.27 It will be interesting to test whether the PE repeat is one of the major epitopes recognized by this antibody.…”
Section: Potential Regulatory Regions Of Ryrs Activitymentioning
confidence: 97%
“…According to our molecular model of the ryanodine receptor [3], this expressed protein has the channel region containing four putative transmembrane segments (Ml-M4), but lacks the 'foot' region. Furthermore this protein is thought to hold the region around amino acid residue 4500 which is suggested to be involved in Ca2' binding and calcium-induced calcium release in the skeletal muscle ryanodine receptor [26,27]. A possible scheme for the expression of the skeletal muscle ryanodine receptor gene is shown in Fig.…”
Section: Expression Of the 3'-terminal Portion Of Thementioning
confidence: 99%